Kajian Semiotika Budaya: Pendidikan Masyarakat melalui Media Mural di SDN Ketintang I Surabaya - Amalia Hartiningrum (LPPM STIKI Malang, 2025)
Visual signs containing messages are often found in mural works in Surabaya, such as on the walls of residents' houses, offices and protocol street walls as a means of communication and expression of the artist. The purpose of this article is to display visualization in the form of murals in Elementary Schools, precisely SD Negeri Ketintang 1 Surabaya in order to see the impact of community education around it. The structure of signs in mural media is studied using semiotics and the function of murals in community education. Data collection methods used include observation, documentation and field studies, the approach used through semiotic studies. The object is the mural on the wall of SD Negeri Ketintang 1 Surabaya. Spectators consist of people who live near the location of the mural. The results of the study obtained are that the form of murals in SD Negeri Ketintang 1 Surabaya tends to display a narrative image style with a hero theme that is adjusted to the identity of the hero city, the nickname of Surabaya. The structure of the mural has a fairly high readability both in terms of visuals and text. The use of various colors ranging from basic colors, to secondary colors and shadows on the visuals, while the text only uses black. The existence of murals is felt by spectators to reach individuals, but the understanding of each individual is the result of the relationship between visual perception and the concept adopted. The process of community education can only reach individuals but has not been able to become a collective awareness that can move society to change its behavior.